El trazo del horizonte - Arango González, Alfonso, (Colección Tesis de posgrado., 2018)
The book explores the way in which five contemporary architects (Alberto Campo Baeza, Sverre Fehn, Peter Zumthor, Frank Gehry, Peter Eisenman) have conceived and represented that elusive line, as if compiling the cosmogonic stories of five distant cultures on the sky and the earth, and their translation in the built space. The presence or absence of the outline of the horizon in the architectural sketches gives clues as to how these architects approach, through drawing, architecture and their relationship with the world understood between the sky and the earth. This book also illustrates, in order to broaden the panorama, how five cultures-scattered throughout time and geography-have conceived and represented the original cosmogonic relationship between heaven and earth, a relationship that has shaped their thought, its customs and its architectures.